1987
DOI: 10.1159/000217530
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Thomsen-Friedenreich Antibody Subpopulations from Normal Human Serum

Abstract: Thomsen-Friedenreich (TF) antibodies were prepared from human serum by different enrichment procedures. This resulted in three antibody preparations all of which agglutinated neuraminidase-treated erythrocytes. On the other hand, each of the three antibody populations showed a distinct specificity pattern. Anti-TF1 antibodies could be inhibited in the hemagglutination inhibition assay by asialofetuin, asialotransferrin, asialoglyco-phorin and asialomucin. The sialylated form of these glycoproteins showed no in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…Several groups have demonstrated the presence of TF antigens in carcinoma as well as in lymphoma cells [1,[3][4][5][6]. Antisera and lectins were used for their detection and it was shown that these reagents bind to differ ent epitopes on the cell membrane or to structures in the cytoplasm [3,14], The use of peanut agglutinin in breast cancer tissue resulted in an overall staining of cancerous tissue regardless of tumor stage as well as structures in normal tissue [15,16] [unpubl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have demonstrated the presence of TF antigens in carcinoma as well as in lymphoma cells [1,[3][4][5][6]. Antisera and lectins were used for their detection and it was shown that these reagents bind to differ ent epitopes on the cell membrane or to structures in the cytoplasm [3,14], The use of peanut agglutinin in breast cancer tissue resulted in an overall staining of cancerous tissue regardless of tumor stage as well as structures in normal tissue [15,16] [unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…TF antigens are defined as epitopes which are present on human erythrocytes after removal of surface sialic acid. They can be detected by antisera, monoclonal anti bodies (Mab) or peanut agglutinin [1,[3][4][5][6], Several lines of evidence suggest that the expression of TF antigens might have a role in organotropic metastasis of tumor cells into the liver. Most of the TF antigens carry terminal galactose residues and are, there fore, believed to interact with the asialogly coprotein receptor of the liver [7] as shown for lymphocytes and erythrocytes which ac cumulate in the liver after neuraminidase (NDA) treatment [8], Another example is the selective adherence of a highly metastatic variant of a mouse lymphoma cell line to syngeneic hepatocytes in contrast to its poorly metastatic parental line [9], The elu cidation of antigenic structures associated with metastasis is of clinical importance, be cause the intensity of the antigen on the tumor cells or the number of cells in the sur gically removed primary tumor expressing the antigen might correlate with the biologi cal behavior of tumor cells and might, final ly, lead to a better estimate of prognosis for the patients.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of such autoantibodies against GP (as well as antibodies directed against peptide epitopes unmasked by desialylation of GP) in human sera has to our knowledge not yet been described in the literature. It has to be considered if aGP is used as an immunosorbent for the isolation of anti-TF antibodies, as has been done in previous publications [15,19,20,22,23], and it underscores the advantage of the immunosorbent used in our study.…”
Section: Discussionmentioning
confidence: 97%
“…This method was also used by Wolf et al [20]. They obtained two fractions with different specificities, in which the hemagglutination by one of them was not inhibited by the TF disaccharide.…”
Section: Discussionmentioning
confidence: 99%
“…Two TACAs that are highly thought of as immune targets are the Thomsen-Friedenreich (TF or T) antigen (Galb1-3GalNAca) and the Tn (GalNAca) antigens [60]. Human blood serum contains natural TF- and Tn antibodies whose subpopulations may bind the corresponding antigens on human tumor cell lines [61, 62]. The high level of anti-TF and Tn IgG, observed in some patients with cancer, may be a sign of an ongoing immune response, as indicated by the switching of antibody to the IgG-class.…”
Section: Carbohydrates and The Immune Surveillance Paradigmmentioning
confidence: 99%